2016
DOI: 10.1155/2016/6383240
|View full text |Cite
|
Sign up to set email alerts
|

Restoring Spinal Noradrenergic Inhibitory Tone Attenuates Pain Hypersensitivity in a Rat Model of Parkinson’s Disease

Abstract: In the present study, we investigated whether restoring descending noradrenergic inhibitory tone can attenuate pain in a PD rat model, which was established by stereotaxic infusion of 6-hydroxydopamine (6-OHDA) into the bilateral striatum (CPu). PD rats developed thermal and mechanical hypersensitivity at the 4th week after surgery. HPLC analysis showed that NE content, but not dopamine or 5-HT, significantly decreased in lumbar spinal cord in PD rats. Additional noradrenergic depletion by injection of N-(2-ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 67 publications
1
14
1
Order By: Relevance
“…The change of nociception was reported in the studies using unilateral PD model rats [46]. And, mechanical allodynia or hypersensitivity were reported in the studies using bilateral PD model rats [79]. Our results are consistent of results of these studies in that the change of nociception occurred.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The change of nociception was reported in the studies using unilateral PD model rats [46]. And, mechanical allodynia or hypersensitivity were reported in the studies using bilateral PD model rats [79]. Our results are consistent of results of these studies in that the change of nociception occurred.…”
Section: Discussionsupporting
confidence: 90%
“…These studies, including ours, involved the use of unilateral PD model rats. In few studies, nociception has been examined with the usage of bilateral PD model rats [79]. Because idiopathic PD is bilateral, bilateral PD model rats are more closely to the pathological condition in humans [10].…”
Section: Introductionmentioning
confidence: 99%
“…Taylor and colleagues found that bilateral microinjection of the D 2 -like receptor agonist quinpirole in nucleus accumbens inhibits persistent nociception in the formalin test in rats. 15 In experimental conditions the analgesic effect of pramipexole is demonstrated in animals with artificially-induced PD 13,16 but not in naïve rats. Cao LF et al found that pramipexole reduces thermal, but not mechanical pain hypersensitivity in rats with 6-OHD-induced model of PD.…”
Section: Discussionmentioning
confidence: 99%
“…12 Pramipexole is D 2 /D 3 dopamine receptor agonist found to inhibit thermal hypersensitivity in rats with 6-hydroxydopamine (6-OHDA) model of PD. 13 Clinical trials demonstrated that this drug decreases pain in patients with fibromyalgia. 14 Tolcapone is an inhibitor of dopamine metabolising enzyme catechol-O-methyltransferase (COMT).…”
Section: Introductionmentioning
confidence: 99%
“… 16 19 Also, because of its unique noradrenergic features, tapentadol may improve pain in PD by restoring the spinal noradrenergic inhibitory tone. 15 , 20 , 21 …”
Section: Introductionmentioning
confidence: 99%